Ecology and Diversity of Marine Decapods - Briones-Fourzán, Patricia; Hendrickx, Michel E. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a collection of papers on different aspects of the diversity and ecology of marine decapod crustaceans, including integrative taxonomy and genetic diversity, DNA barcoding to match larvae to adults, predator-prey interaction, coral-crab symbiosis, Sargassum-shrimp symbiosis, population dynamics of pelagic shrimps, diversity and distribution of oceanic larvae, spatial distribution of crabs, biodiversity of lobsters, and ecology of cave decapods. These contributions illustrate the variety of life forms, habitat use, and interspecific relationships exhibited by decapod crustaceans, one of the most diverse and abundant marine taxa.